Critical Analysis of Information Sources and Channels Preferred by Vegetable Growers of Haryana. - S., Gondkar Sachin.; Pooja, Chaudhary; Joshi, Vister; Sherawat, P. S. (Indian Journal of Extension Education, 2015)
The present study was conducted in 2014-15 to study the rapidity, utilization and credibility pattern of information sources  and channels by the vegetable growers in Haryana. The 160 vegetable growers from four districts of Haryana were  interviewed. The study reported that personal localite sources like neighbours, friends, progressive and opinion farmers  were playing important role in transfer of vegetable production technologies to the vegetable growers. These sources with  high credibility were widely used by majority of the respondents. While SMS and Scientists were perceived as most rapid  source of information for transfer of technology. The most revealing finding of the study is that ADO/BAO had lost their  credibility among the farmers while the input suppliers and agents of commercial seed, fertilizers, plant protection, etc.,  played a critical role in information network of vegetable growers , however their credibility is low. It was important to  note that scientists and SMSs were perceived a much credible source of information by farmers, however these sources  were less accessible to the farmers. Further, the increasing literacy rate and easy accessibility of the mass media channels  resulted in increased utilization of these media by the farmers.
Keywords: Information sources and channels; vegetable growers; credibility